Exploring the magnitude and predictors of the long-term psychological impact of COVID-19 on frontline healthcare workers in Vietnam: a multi-center, cross-sectional study - Hong Trang Nguyen; Bich Thuy Duong; Thinh Toan Vu; Sophia Lin; Tri Nugraha Susilawati; Ba Tam Nguyen; Minh Cuong Duong (BMC Health Services Research)
Abstract Background The detrimental impacts of COVID-19 on the mental well-being of frontline healthcare workers (HCWs) have been well studied. However, the long-term trajectory of their mental well-being remains relatively unexplored. We examined the magnitude and predictors of the psychological impact of COVID-19 on frontline HCWs during the transition into the “new normal” phase. Methods A cross-sectional survey was performed on frontline HCWs at two largest designated COVID-19 hospitals in Ho Chi Minh City between May and November 2022. A self-administered questionnaire captured participants’ demographic characteristics and psychological distress including depression, anxiety, and insomnia. Multivariable logistic regression models were used to examine factors associated with psychological distress. Results Among 462 HCWs, 85.3% self-reported having good, very good, or excellent mental health before their COVID-19 deployment, compared to 40.7% during the deployment and 55.6% at the time of the study. The prevalence of moderate-to-severe depression was 26.8%, anxiety (20.8%), insomnia (23.4%), and overall psychological distress (73.2%). Predictors for depression included pre-existing physical (adjusted odds ratio [aOR] = 2.09, 95%CI 1.03–4.22, P = 0.04) and mental health (aOR = 3.59, 95%CI 1.31–9.84, P = 0.01) conditions and being deployed during the 3rd (aOR = 6.28, 95%CI 1.12–35.08, P = 0.04) and 4th (aOR = 5.01, 95%CI 1.08–23.16, P = 0.04) COVID-19 wave. Those with mental health conditions before the deployment (aOR = 3.95, 95%CI 1.42–11.0, P = 0.008) were more likely to report anxiety symptoms. Predictors for insomnia included physical health conditions before the deployment (aOR = 2.73, 95%CI 1.37–5.44, P = 0.004), working at field hospitals (aOR = 2.44, 95%CI 1.43–4.16, P = 0.001), and currently being deployed to respond to COVID-19 (aOR = 0.35, 95%CI 0.19–0.67, P = 0.001). Conclusions Given the substantial impact of COVID-19 deployment on HCWs’ long-term mental well-being, comprehensive mental health support strategies are urgently needed. As HCWs may overlook their mental health issues, a screening program with psychological support services should accompany them early in future pandemics. Further nationwide studies with longer follow-ups are necessary to understand the full extent of psychological distress among frontline HCWs in Vietnam.